1001 inventions & awesome facts from Muslim civilization. (National Geographic kids., 2012)
Traces centuries of invention and technological innovation in the Muslim world, revealing how Muslim intellectuals built elephant water clocks, drew detailed world maps, and built colossal architectural structures.